O Reiki na Faced: espiritualidade e cultura de paz no Projeto de Extensão de Educação para a paz da Faculdade de Educação da UFC - Nascimento, Dário Gomes do (2019)
Can the implementation of a reiki activity at the Faculty of Education - FACED of the Federal University of Ceará - UFC contribute to the health promotion of undergraduate and graduate students at this institution, positively influencing their educational process? In order to answer this question, we carried out this research, which has the general objective of observing how the reiki activity at this institution materialized in practice, in what way it happens and how it was implemented. The specific objectives are to: 1- collect and analyze data about the impressions of FACED undergraduate and graduate students with regard to their participation in the reiki project; 2 - interpret the data collected related to the implications of reiki therapy in the subjects seen in the light of Ken Wilber's (2000) compression of Spirituality and Integral Human Being; 3 - analyze the relationship between reiki therapy and culture of peace. With regard to the methodology, it is an applied and exploratory research, with a qualitative approach, being an action research. Bibliographic and documentary research and digital media were used. We made observation records, data collection using questionnaires and interviews with 26 students. Eleven students and 5 therapists answered the questionnaire prepared using the Google Drive form and sent through the WhatsApp application. Data analysis was done through content analysis (BARDIN, 1997). The central categories of the study are: Reiki (DE'CARLI, 2006; CORDEIRO, 2016), Spirituality (ERVEDOSA, 2004; WILBER, 2007 and 2008), and Culture of Peace (MATOS, 2016; GUIMARÃES, 2006, 2011; JARES, 2002, 2007). The research subjects are undergraduate and graduate students at FACED / UFC attended by the reiki activity at FACED and students who are volunteer therapists and work in this activity. We restricted the public to students attended in 2018 (26), although the demand for the service is much broader with teaching staff and administrative technicians, outsourced employees and the general population. As for students who are volunteer therapists, we highlight that a part of this group is made up of undergraduate students from UFC who were initially served, and that throughout the project they became therapists. The results of the research demonstrate that taking care of oneself and the other promotes good coexistence, being, therefore, a culture of peace practice. In addition, reiki proved to be a means of promoting spiritual experiences, both translative and transformative, as well as being a health promotion tool, while its participants feel calmer, lighter and less tense. Participants also reported that it was easier to focus on academic activities.